The Effect of Heat Treatment on Specific Gravity and Organoleptic Properties of Jack Bean (Canavalia ensiformis) Milk - Hadi Santosa; Ivan Gunawan; Dian Trihastuti; Nicole Levina Celestina (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
AbstractMost of the dairy products sold in the market in Indonesia are animal milk but those products cannot be consumed by people with lactose intolerance and allergies. Plant-based milk is an alternative substitute for animal milk, and the most widely known is soy milk, but the production of soybeans in Indonesia is low. Jack beans (Canavalia ensiformis) are an alternative raw material substitute for plant-based milk. Meanwhile, the protein content of jack beans is similar to soybeans, but it is not popular as a food ingredient. This study aims to obtain the acceptable combination factors in processing jack bean milk. A full factorial design experiment was conducted to analyze the effect of temperature and heating duration on the specific gravity of jack bean milk and its organoleptic properties such as color, aroma, taste, and texture. The results showed that the temperature and heating time influenced the specific gravity and organoleptic properties of jack bean milk. In addition, the best combination of factors and levels is at a heating temperature of 100 °C for 20 minutes, which results in the specific gravity of jack bean milk, which is 1.0758.Keywords: design of experiments, jack beans, plant-based milk AbstrakSebagian besar produk susu yang dijual di pasaran di Indonesia adalah susu hewani, tetapi produk tersebut tidak dapat dikonsumsi oleh penderita intoleransi laktosa dan alergi. Susu nabati dapat menjadi alternatif pengganti susu hewani. Susu nabati yang paling dikenal adalah susu kedelai, tetapi produksi kedelai di Indonesia masih rendah. Kacang koro pedang (Canavalia ensiformis) dapat menjadi alternatif pengganti dalam pembuatan susu nabati. Kacang koro pedang belum dikenal sebagai bahan makanan meskipun kandungan protein dalam kacang koro pedang mirip dengan kacang kedelai. Tujuan penelitian ini adalah untuk menemukan kombinasi faktor dalam mengolah kacang koro pedang yang dapat diterima masyarakat. Percobaan faktorial dalam rancangan acak lengkap dilakukan untuk melihat pengaruh suhu dan lama waktu pemanasan terhadap berat jenis dan karakteristik organoleptik susu koro pedang, seperti warna, aroma, rasa, dan tekstur. Hasil penelitian menunjukkan bahwa suhu dan lama waktu pemanasan mempengaruhi berat jenis dan karakteristik organoleptik susu koro pedang. Kombinasi faktor dan level terbaik diperoleh pada pemanasan dengan suhu 100 °C selama 20 menit yang menghasilkan berat jenis 1,0758.Kata kunci: kacang koro, rancangan percobaan, susu nabati